Physical, Mechanical and Acoustic Characteristics of Anogeissus leiocarpus, Manilkara multinervis and Cylicodiscus gabunen-sis Woods Marketed in Benin in West Africa - Hounlonon , Montcho Crépin; Kouchadé , Adéyèmi Clément; MEDEHOUENOU, Alexis Enagnon; GOHOUNGO, Vincent; HOUNGAN, Aristide Comlan; KOUNOUHEWA, Basile Bruno (International Journal of Engineering and Technology, 2022)
Wood is a material used in construction, in instrument making, etc. In Benin, for heavy construction and construction on wetland, species with high technological characteristics are imported. But the performance of these imported species compared to local indigenous or exotic species remains to be verified. Thus, it is necessary to determine the basic technological properties of these species. It is within this framework that we have, on 500mmÃ—20mmÃ—20mm prismatic wood specimens of Anogeissus leiocarpus, Manilkara multinervis and Cylicodiscus gabunensis, used the acoustic method BING (Beam Identification by Non-destructive Grading) of CIRAD-Forest to determine the density Ï, the moduli of Young's modulus E, shear modulus G and the internal friction tanð›¿ and then evaluated the modulus of specific stiffness E/Ï. On other 20 mm edge cubic specimens, we evaluated the reference physical properties of density, infradensity, total shrinkage, radial shrinkage, tangential shrinkage and shrinkage anisotropy. It appears that the wood of Anogeissus leiocarpus and Manilkara multinervis present better physico-mechanical characteristics than those of Cylicodiscus gabunensis. Anogeissus leiocarpus and Manilkara multinervis are very dense woods with physico-mechanical characteristics better than those of most Benin's popular species. The average modulus of elasticity in bending of these two species is higher than 12000 MPa while that of Cylicodiscus gabunensis is 10713 MPa. In compression all these species have an average modulus of elasticity above 14100 MPa.Â  Cylicodiscus gabunensis wood tested is light with a lower shrinkage anisotropy than the other two species studied and have excellent acoustic properties. Its average specific stiffness (14 GPa) is higher than that of the other two species studied (12 GPa). The good physical-mechanical and acoustic properties of these species show that they are good structural timbers with also good potential for instrument making and acoustic insulation.Keywords: BING; Construction; Infradensity; Modulus of elasticity; Shrinkage anisotropy; Timber.